New timbres of St. Catherine’s carillon - BUDZYŃSKI, G.; SANKIEWICZ, M.; SZYCHLIŃSKI, G. (Archives of Acoustics, 2000)
St. Catherine’s carillon, the largest instrument of its kind in Poland, deserves special attention due to its particular acoustic properties. They were investigated in detail and relevant results reported earlier. Recently, the acoustic possibilities of the carillon and its sound repertory has been significantly augmented thanks to twelve new bells added to the 37 existing so far, and the newly installed keyboard, enabling the carillonist direct exciting of bell sounds. Thanks to the enlarged carillon sound scale and the direct mechanical coupling of keyboard keys to bells, the carillonist gains an enriched possibility of creating new chords and complex timbres resulting in several bells being struck either together or subsequently. These timbres were actually investigated with the same method and equipment as applied during the former investigations, mentioned above. The selected carillon sounds were recorded and the recorded samples analyzed digitally by means of dedicated computer software programs. The results confirm the high quality of the enlarged part of the carillon, comparable to the very high quality of the instrument existing so far. Conclusions concerning particular properties of the St. Catherine carillon are presented at the end of the paper.